Mathematics learning motivated by computer attitude and social media engagement - Almagro, Ronald E.; Edig, MA. Melanie (Journal of Social, Humanity, and Education, 2024)
Purpose: This study aimed to investigate the impact of computer attitudes and social media engagement on students' motivation to learn mathematics. Methodology: The study followed a descriptive-correlational approach involving 181 Grade 11 students from three private schools. Questionnaires and statistical tools were used to gather the data. Results: The results revealed a clear connection between positive computer attitudes and active social media engagement. Moreover, significant evidence has indicated the effectiveness of motivated strategies in improving math learning outcomes. Interestingly, while computer attitudes alone did not significantly influence these strategies, social media engagement had a notable impact. Limitations: Limited generalizability (specific region, Grade 11 private school focus). Contribution: Enhances understanding of the link between computer attitude, social media, and motivated strategies in math learning. Emphasize integrating social media to boost motivation and learning outcomes. Valuable for students, teachers, administrators, and officials in shaping effective strategies. Novelty: One key takeaway is the importance of integrating social media platforms into educational practices to enhance motivation and improve learning outcomes. This study provides valuable insights for students, teachers, administrators, and policymakers as they work together to shape effective learning strategies. Moreover, it offers a unique perspective on the role of technology and social media in fostering motivation and enriching learning experiences.